Fostering the properties of Zr0.8Sn0.2TiO4 (ZST) ceramics via freeze granulation without sintering additives - Olhero, S. M. (2017)
The present paper reports the overall benefits of freeze granulation for enhancing the properties of zirconium tin titanate Zr0.8Sn0.2TiO4 (ZST) ceramics in the total absence of sintering additives. The ZST powder was synthesized by solid state reaction and attrition milled in ethanol for 10 h. This starting non-granulated powder (NG-ZST), without and with 1 wt% ZnO as sintering additive, was used to consolidate green bodies by dry pressing. The pure ZST powder was also dispersed in aqueous media to obtain stable suspensions with high solid loadings. Free flowing spherical homogeneous granules were prepared by freeze granulation and used to consolidate ZST green bodies by dry pressing (FG-ZST). The effects of processing variables and sintering temperature (1300-1450 degrees C) on densification and on the structural, mechanical and electrical properties of ZST ceramics were systematically investigated. Our study clearly reveals the superior properties of FG-ZST ceramics, which derive from an enhanced sintering behaviour associated with the absence of sintering additives.